2014
DOI: 10.1590/0074-0276130483
|View full text |Cite
|
Sign up to set email alerts
|

[No Title Available]

Abstract: Malaria is still a primary health problem in Colombia. The locality of Tierradentro is situated in the municipality of Montelíbano, Córdoba, in the northwest of Colombia, and has one of the highest annual parasite index of malaria nationwide. However, the vectors involved in malaria transmission in this locality have not yet been identified. In this study, the local anthropophilic Anopheles composition and natural infectivity with Plasmodium were investigated. In August 2009, 927 female Anopheles mosquitoes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
(24 reference statements)
2
4
0
Order By: Relevance
“…albimanus , found in every sampled locality and both seasons. This species is of epidemiological importance since it is considered as a primary vector in the low coastal regions of the Caribbean and Pacific coasts in Colombia [17], and our results contribute the first records of this species in two localities, Los Cordobas and Puerto Libertador. The second most abundant species, An.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…albimanus , found in every sampled locality and both seasons. This species is of epidemiological importance since it is considered as a primary vector in the low coastal regions of the Caribbean and Pacific coasts in Colombia [17], and our results contribute the first records of this species in two localities, Los Cordobas and Puerto Libertador. The second most abundant species, An.…”
Section: Discussionsupporting
confidence: 60%
“…Anopheles pseudopunctipennis was found infected with P. vivax; this species was previously collected in the south of Córdoba but always in lower abundances compared to those found in this study [16, 17]; this species is here reported for the first time in the northern part of the department, in the municipality of Moñitos. This scenario could be reflecting the effect of the sampling methods, using exclusively traps for insect collection, but might be providing valuable information that should be deepened regarding changes in the ecology of disease transmission related to the current changes in malaria epidemiology recorded in the Americas [2].…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations